(untitled) (Tikrit Journal of Veterinary Science, 2024)
The present study was aimed to evaluate the efficiency of E. globulus on growth performance on Common carp. For this purpose, 100 fingerlings of Cyprinus carpio weight ranged between 65.18 -65.36 g were randomly distributed into five treatment groups. Fish were fed with different E. globulus concentrations: 0.25% (T2), 0.5% (T3), 0.65% (T4) and 1% (T5). The first group (T1) was serve as control group without any addition of E. globulus . After 28 days of feeding, blood samples were collected for determination of hematological and biochemical parameters. The feed trail results indicate that treatment groups supplemented with E. globulus had significantly greater growth rates, hematological and biochemical parameters (P≤0.05) as compared to the control group. The highest values were observed in the T4 supplement with 1.5 percent E. globulus. Our findings indicate that the food supplement of E. globulus enhanced the hematological, biochemical, and growth rate parameters of C. carpio. This shows that the carp are using this feeding supplement.